PENGARUH DEBT TO EQUITY RATIO, NET PROFIT MARGIN, RETURN ON EQUITY, QUICK RATIO TERHADAP EARNING PER SHARE PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2014-2017 - Moniq Aditya Dhira Yanutama; Deny Ismanto (Jurnal Fokus Manajemen Bisnis, 2018)
This research was conducted with the aim of empirically testing the effect of Debt To Equity Ratio, Net Profit Margin, Return On Equity, Quick Ratio Against Earning Per Share for Companies in the Textile and Garment Sub Sector Listed on the Indonesia Stock Exchange for the 2014-2017 Period. The research period was carried out for 4 (four) years, namely 2014-2017. This type of research is causal research, that is, this study looks for a causal relationship between independent variables and the dependent variable. The population in this study were all textile and garment sub-sector companies listed on the IDX, which were 18 textile and garment sub-sector companies. The sample in this study was obtained by purposive sampling method. Based on existing criteria, 14 textile and garment sub-sector companies were obtained. Hypothesis testing is done by multiple linear regression analysis. The results of hypothesis testing are done partially, namely the t test shows that DER has a sig value. t is 0,000, the regression coefficient (B) is 38,611 and t is calculated: 4,796, the result states that DER has a significant positive effect on EPS. NPM has a sig value. t is 0,000, regression coefficient (B) is 12,726 and t is calculated: 29,230, the result states that NPM has a significant positive effect on EPS. ROE has a sig value. t is 0.002, the regression coefficient (B) is -1.485 and t is calculated: -3.3321, the result is that ROE has a significant negative effect on EPS. QR has a sig value. t is 0.480, the regression coefficient (B) is -13.095 and t is calculated: -0.712, the result is that QR has a negative effect that is not significant for EPS.